Stereotypic pacing response of captive leopards (Panthera pardus Linnaeus) to feeding and olfactory enrichment in Malaysian Zoos - Juhari, Farah Hanis (2015)
Individual animals associated with stereotypy behaviour are considered more stressful compare with the non-stereotyper, which the former’s welfare is less concern. This study postulates that animals showing low stereotypic pacing were as stressful as the high stereotypic individuals. Three captive leopards from Taiping Zoo and two captive leopards from National Zoo were used as subject animals. Data collections were performed on husbandry and management; behavioural studies and two environmental enrichments that were feeding and olfactory enrichment, were implemented. The level of stereotypic pacing was divided into two categories, high and low stereotypic groups, based on the individuals’ deviation from the mean of stereotypic pacing (13.5%). The high stereotypic group performed better during feeding enrichment while the low stereotypic group was more active during the olfactory enrichment. However, none of these groups showed significant reduction in stereotypic pacing and inactive behaviour, which may indicate that both groups were adversely affected by the suboptimal captive conditions. Exploratory, locomotory and playing behaviour were significantly increased during feeding enrichment and no habituation occurred during presentation. Olfactory enrichment significantly increased locomotory behaviour and social behaviour but active behaviour was significantly waned on the fourth day of enrichment. Individuals’ characteristics which were dominancy, type of born and positive relationship with caretakers may influence the performance of stereotypic pacing. Results from this study are crucial for the evaluation of the welfare of captive leopards and to highlight the welfare of animals showing low stereotypic behaviour may be just as vulnerable as the ones demonstrating high stereotypic behaviour.